Crystal plasticity-based finite element modeling of twin transmission across grain boundaries in magnesium. (March 2022) - Sun, Yingjun; Zhou, Kecheng; Qiao, Hua; Xin, Renlong; Wang, Huamiao; Wu, Peidong
Abstract: For polycrystalline materials with the deformation mechanism of twinning, the interaction between the twins and grain boundaries are substantial to their deformation behavior. In the current work, the twin transmission across the grain boundaries in a magnesium bicrystal is investigated with the aid of crystal plasticity finite element model. The influencing factors, such as the crystallographic orientation of grains, GB misorientation, critical resolved shear stress (CRSS), dislocation slip, and twin-induced stress relaxation are considered. The commonly used geometric factors of macroscopic Schmid factor (MSF), geometric compatibility factor (GCF), and the lately proposed composite Schmid factor (CSF) are assessed by comparing the simulations and available experiments. The CSF can interpret the twin transmission better than either the MSF or the GCF. Moreover, the available twin transmission ability characterized in terms of the fraction of twin transmitted GBs is well captured by the CSF.